Reframing Resistance: Religious Branding and New Hegemonies in Instagram Content of @ShejekIndonesia - Ramadhani, Jihan Aulia (Sabda: Jurnal Kajian Kebudayaan, 2025)
This study examines how Shejek, a Sharia-based ride-hailing platform for Muslim women, constructs religious identity and reframes resistance within the context of Indonesia’s digital economy. Unlike mainstream services such as Gojek and Grab, Shejek integrates Islamic principles—including the avoidance of ikhtilat (unrestricted interaction between marriageable individuals) and khalwat (seclusion of a man and a woman in private spaces)—to market itself as a safer and more religiously appropriate transportation option. Through a qualitative content analysis of Shejek’s Instagram posts from 2023 to 2024, this research explores how narratives of urban fear, piety, and gendered safety are strategically deployed in digital branding.Findings reveal that rather than presenting a direct resistance to patriarchal structures, Shejek negotiates empowerment by embedding Islamic values into the platform economy, thereby creating a new form of hegemony. Its use of religious branding and fear-based narratives fosters emotional loyalty and market differentiation but also risks reinforcing exclusionary norms. This study contributes to critical discussions on religious commodification, gendered digital spaces, and the dynamics of cultural power in Southeast Asia’s sharing economy.